The Effect of Nutritional Interventions to Improve the Nutritional Status of Cancer Patients Undergoing Chemotherapy - Wahyuningsih, Rita Sri; Allenidekania, Allenidekania (Indonesian Journal of Global Health Research, 2024)
Cancer is a catabolic inflammatory disease that causes patients to experience frequent weight loss, or even cachexia in severe cases. Malnutrition in cancer patients impairs quality of life and therapeutic response, further leading to a poor prognosis. This study aims to determine various types of nutritional interventions that can improve the nutritional status of cancer patients undergoing chemotherapy. The research method used is a systematic review through electronic databases and websites, namely PubMed, Scopus, ProQuest, and MedLine. The keywords used for the search were "Nutrition Intervention" AND "Nutritional Status" AND "Cancer patients" OR "Chemotherapy patient". The search for supporting articles was limited to the years 2015-2023, resulting in the identification of 953 articles. After identification, screening, and extraction according to the inclusion and exclusion criteria, 12 articles were included. The research results showed that from 12 research articles, it was found that providing nutritional interventions could be in the form of oral nutritional supplements, omega 3 supplements, as well as other supplements such as propolis, broccoli supplements, and additional parenteral nutrition at home. Providing this nutritional intervention can improve the nutritional status of cancer patients undergoing chemotherapy.